2019
DOI: 10.1080/15384101.2019.1667189
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Notch signal pathway suppresses the activation of neurotoxic A1 astrocytes after spinal cord injury

Abstract: Spinal cord injury (SCI) is a catastrophic disease which has complicated pathogenesis including inflammation, oxidative stress and glial scar formation. Astrocytes are the most abundant cells in central nervous system and fulfill homeostatic functions. Recent studies have described a new reactive phenotype of astrocytes, A1, induced by inflammation, which may have negative effects in SCI. As the Notch signaling pathway has been linked to cell differentiation and inflammation, we aimed to investigate its potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 70 publications
9
73
0
Order By: Relevance
“…The in vivo blockade of A1 astrocyte formation through a total KO of C1qa/TNF/IL1a prevents the death of CNS neurons. Similar to the results in brain injury models, a recent study demonstrated the existence and neurotoxic function of A1 astrocytes in an SCI model (Qian et al, 2019). In this study, the immunofluorescence of C3 (a marker of A1 astrocytes) increases as early as 3 days after SCI.…”
Section: The Neurotoxic Phenotype Of Reactive Astrocytessupporting
confidence: 86%
See 1 more Smart Citation
“…The in vivo blockade of A1 astrocyte formation through a total KO of C1qa/TNF/IL1a prevents the death of CNS neurons. Similar to the results in brain injury models, a recent study demonstrated the existence and neurotoxic function of A1 astrocytes in an SCI model (Qian et al, 2019). In this study, the immunofluorescence of C3 (a marker of A1 astrocytes) increases as early as 3 days after SCI.…”
Section: The Neurotoxic Phenotype Of Reactive Astrocytessupporting
confidence: 86%
“…The direct relationship between the reduction of A1 astrocytes and functional recovery also needs more proof. Qian et al (2019) changed the astrocytic state through interventions on the Notch-STAT3 axis, which was quite different from the study of Liddelow et al (2017). Regardless, these findings suggest that: (1) the existence of a neurotoxic/neuroprotective phenotype of astrocytes in the context of SCI is reasonable;…”
Section: The Neurotoxic Phenotype Of Reactive Astrocytesmentioning
confidence: 61%
“…Primary microglia were obtained as previously reported [57,58]. Briefly, brains were removed from newborn mice (1-3 days old) and carefully cut into 0.5-1-mm 3 pieces.…”
Section: Cell Culture and Hypoxia Treatmentmentioning
confidence: 99%
“…After SCI, the limited regenerative capacity of the adult mammalian spinal cord has been attributed to the formation of cavities and glial scars that interrupt the ascending and descending pathways [17][18][19]. Now, NSC transplantation is considered an appropriate choice for treating SCI [20].…”
Section: Discussionmentioning
confidence: 99%